Amphotericin B derivative blocks human immunodeficiency virus type 1 entry after CD4 binding: effect on virus-cell fusion but not on cell-cell fusion. - Pleskoff, O (1995)
The antiviral effect of MS8209, an amphotericin B derivative, was studied in CD4+ cells transfected with a lacZ gene inducible upon human immunodeficiency virus type 1 (HIV-1) infection. MS8209 was shown to block virus entry after receptor binding and probably before virus-cell membrane fusion, but it had no effect on syncytium formation, although both processes are mediated by HIV-1 envelope proteins and CD4.